Pluripotential hemopoietic stem cells in adult mouse brain. - Bartlett, P F (1982)
Single cell suspensions of adult mouse brain were shown to contain large numbers of pluripotential hemopoietic stem cells as detected by the ability to form hemopoietic colonies in the spleens of irradiated hosts. These colony forming unit, spleen (CFU-s) cells derived from brain gave rise to colonies identical in morphology and histology to those of bone marrow-derived CFU-s. The average number of CFU-s obtained per 10(5) dissociated adult brain cells was 14, whereas other adult tissues such as lung, kidney, heart, and thymus contained insignificant CFU-s levels when tested. As the level of CFU-s in adult blood is less than 1 per 10(6) nucleated cells, blood contamination does not contribute to the high levels found in adult brain. Individual spleen colonies isolated from irradiated CBA (H-2k) recipients injected with (BALB/c x CBA)F1 (H-2d x H-2k) brain cells were shown by immunofluorescence to contain cells bearing surface H-2d molecules, thus indicating that the colonies arose from the brain cell inoculum and were not endogenously derived. The surface phenotype of brain- and bone marrow-derived CFU-s was found to differ in that brain CFU-s could be inhibited by prior incubation with a monoclonal antibrain antibody B2A2, whereas bone marrow CFU-s were not. Further differences were found between brain and bone marrow CFU-s in the congenitally anemic Wf/Wf mice. These mice were shown to have a very few CFU-s in the adult bone marrow, whereas the brain contained normal adult levels. The large number of hemopoietic stem cells in the brain may indicate an essential requirement for the continual generation of cells such as microglia or phagocytic cells, without the disruption of the blood-brain barrier.